2005
DOI: 10.1002/ffj.1508
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil ofPerovskia abrotanoides Karel. growing wild in Iran

Abstract: The chemical composition of the volatile oil from aerial parts of Perovskia abrotanoides Karel. has been studied by GC and GC-MS. Twenty-nine components (98.9% of the total composition) were identified. 1,8-Cineole (32.4%), myrcene (13.0%), α α α α α-pinene (10.2%), camphor (9.1%), β β β β β-caryophyllene (7.9%), α α α α α-humulene (6.4%), camphene (5.0%) and α α α α α-bisabolol (2.6%) were found to be the major constituents of the oil. The oil of P. abrotanoides was characterized by a high content of monoterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…Antihelmintic and anti-fungal properties of P. abrotanoides, J. sabina, F. gummosa, and T. carmanicus is due to the presence of many phenolic, flavonoid, and terpinene compounds such as thymol, menthol, sabinene, camphor, 1,8-cineole, verbenone, alpha terpineol, terpinolene, and gamma terpinene have been found in many essential oils of these plants as anti-inflammatory, anti-infective, anti-fungal, antioxidant, anti-tumor, antihelmintic, and anti-pathogenic to treat many infectious diseases such as dermal, vaginal, and urinary infections, arthritis muscle spasm and dysmenorrhea (20)(21)(22)(23)(24)(25)(26). Therefore, our results in this paper and other researches can confirm the traditional consumption of these medicinal plants in North provinces of Iran (Golestan and Semnan) as anti-spasmodic, anti-inflammatory, antihelmintic, antifungal, and anti-infective to treat UTI, vaginal infection, depression, and stress of arthritis and muscle spasm in pregnant women.…”
Section: Vaginal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antihelmintic and anti-fungal properties of P. abrotanoides, J. sabina, F. gummosa, and T. carmanicus is due to the presence of many phenolic, flavonoid, and terpinene compounds such as thymol, menthol, sabinene, camphor, 1,8-cineole, verbenone, alpha terpineol, terpinolene, and gamma terpinene have been found in many essential oils of these plants as anti-inflammatory, anti-infective, anti-fungal, antioxidant, anti-tumor, antihelmintic, and anti-pathogenic to treat many infectious diseases such as dermal, vaginal, and urinary infections, arthritis muscle spasm and dysmenorrhea (20)(21)(22)(23)(24)(25)(26). Therefore, our results in this paper and other researches can confirm the traditional consumption of these medicinal plants in North provinces of Iran (Golestan and Semnan) as anti-spasmodic, anti-inflammatory, antihelmintic, antifungal, and anti-infective to treat UTI, vaginal infection, depression, and stress of arthritis and muscle spasm in pregnant women.…”
Section: Vaginal Infectionsmentioning
confidence: 99%
“…extract and its constituents (terpinen-4-ol, γ-terpinene, carvacrol, verbenone, terpinolene, and sabinene) may be applied as antibacterial, antifungal, and antioxidant agents and moreover as an anticancer agent. Thus the literature has described that the antibacterial and antioxidant activities of P. abrotanoides can depend on its terpenoids and flavonoids (terpinen-4-ol, γ-terpinene, and carvacrol) in essential oil or extract (21,23,24,27).…”
Section: Vaginal Infectionsmentioning
confidence: 99%
“…which is named "sonbolei-kouhsary" or "sonboleikharalood", is one of them. The compositions of the oils of some Stachys species from Iran, such as S. setifera [1], S. ixodes [2], S. persica [3], S. byzanthin [4], S. lanata [5], S. schtscheglee [6], S. pilifera [7], S. lavandolifolia [8,9], and S. laxa [10], have been reported. Stachys species have also been studied in biosystematic and chemotaxonomic studies [11,12].…”
mentioning
confidence: 99%
“…This difference between the oil compositions of one species of Stachys from two different areas can be related to climatological factors (from south to central Iran) and is discussed in phytological studies. S. glutinosa [14] S. balansae [15] S. oblique [16] S. lavandolifolia [17] S. acerosa** S. athorekalyx [18] S. recta [19] S. laxa [10] S. officinalis [9] 0.2 0.3 0. Previous studies on essential oils of members of Stachys genus showed various compositions.…”
mentioning
confidence: 99%
See 1 more Smart Citation